THE ROLE OF TECHNOLOGY TO ENHANCE LEARNING AWARENESS IN SCHOOLS: LITERATURE REVIEW - Aris, Affandy Agusman; Pebriana, Putri Hana; Judijanto, Loso; Ramadhona, Rossa; Lestari, Nana Citrawati; Maq, Mumu Muzayyin (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
The paper aims to look at the role of technology in increasing awareness of learning in schools. This research uses a biographical approach and the type of research used is library research, namely collecting data or scientific writing aimed at research objects or collecting data of a library nature. The data collection technique used is library research. Literature study is a data collection technique used in research by collecting data and research sources through books, journals, magazines, newspapers and others. Technology was created to make all human activities easier in everyday life. Basically, technology plays an important role in fulfilling all human needs, including information and communication. In this case, the need for information is increasingly significant considering technological advances that are currently developing rapidly. The role of information and communication technology is a need that must be met. Information available in various contexts can make it easier for people to fulfill all their needs, one of which is education